Bumetanide Continuous Infusions in Critically Ill Pediatric Patients. Issue 2 (February 2015) - McCallister, Katie M.; Chhim, Rebecca F.; Briceno-Medina, Mario; Shelton, Chasity M.; Figueroa, Mayte; Rayburn, Mark
<x xml:space="preserve">Abstract</x> Objective: Limited data exist for the use of bumetanide continuous infusions in children. The purpose of this study was to evaluate the use of bumetanide continuous infusions in critically ill pediatric patients. Design: This study was an institutional review board approved, single-center, retrospective chart review of 95 patients. Dosing practices were described by rate (μg/kg/hr), duration (days), and previous diuretic use. Efficacy, determined by ability to achieve negative fluid balance and time to reach negative fluid balance, was assessed at 12, 24, and 48 hours. Safety was evaluated based on prevalence of adverse drug reactions. Adverse drug reactions were predefined as serum potassium concentration less than 3 mEq/L, serum chloride concentration less than 90 mEq/L, serum carbon dioxide concentration greater than 35 mEq/L, and serum creatinine increased greater than 1.5 times baseline and above patient-specific normal range. Setting: Le Bonheur Children's Hospital, Memphis, TN. Patients: Critically ill patients who are 18 years old or younger and received bumetanide continuous infusions. A total of 95 patients were included. Interventions: None. Measurements and Main Results: The mean dose of bumetanide was 5.7 ± 2.2 μg/kg/hr (1–10 μg/kg/hr) with a median duration of 3.3 days (0.3–18.5). The total percentage of patients achieving negative fluid balance by 48 hours was 76% with 54% of patients reaching negative fluid balance within 12 hours. Conclusions: This study showed that a bumetanide dose of 5.7 μg/kg/hr was effective in achieving negative fluid balance in the majority of critically ill pediatric patients. Additionally, bumetanide appears to be a safe loop diuretic for use as a continuous infusion at the doses described in critically ill pediatric patients.